EFEKTIVITAS PENURUNAN KADAR SURFAKTAN LINIER ALKIL SULFONAT (LAS) DAN COD DARI LIMBAH CAIR DOMESTIK DENGAN METODE LUMPUR AKTIF - Dwi Adhi Suastuti, Ni G. A. M; Simpen, I Nengah; Ayumi, Nanik (Jurnal Kimia (Journal of Chemistry); Vol. 9, no. 1 Januari 2015, 2015)
This study aimed to determine the ability of the activated sludge in decreasing the concentration of surfactant Linear Alkyl Sulfonate (LAS) and COD in domestic wastewater. The study was begun with the preparation of liquid medium, then mixed with sediment samples to produce the activated sludge. The treatment was carried out by adding the activated sludge to 1250 mL of domestic sewage in the aeration system running for 168 hours. Observations of the LAS and COD values were performed in a period of 6, 24, 72, 120, and 168 hours. The results showed that 5 g activated sludge were able to reduce the values of LAS and COD of 99.70 and 91.08% respectively in 168 hours. The most significant declining values of LAS and COD took place at 6 hours treatment. The rate of declining values of LAS and COD were 82.78 and 55%
Keywords: Activated sludge, LAS, COD, detergent Waste Water